On the Edge of Earth: The Future of American Space Power - Steven Lambakis (University Press of Kentucky, 2013)
On the Edge of Earth: The Future of American Space Power addresses major shortcomings in the defense space policy of the United States and offers recommendations to those who make, influence, and study national security decisions. Its comprehensiveness, references to American political traditions, attention to military and space history, and focus on policy-level considerations distinguish it from other works on the subject. Space is a vital force in the life of the United States, the country's future bound to the development of capabilities for exploiting this environment. Indeed, America's security today depends mightily on its space power. Yet Americans do not spin in orbit alone, nor are potential enemies oblivious to the contributions of satellites to military victory. Equally ambitious and resourceful foreign governments, enabled by the proliferation of space technology and operational expertise, have compelled Washington to take its foreign affairs and security concerns to space. Today the United States is secure in space by default, not because there is a deliberate policy framework and well-resourced, organized, and strategically guided military force to guard national space interests. Security cannot be stable when it exists by accident. History supports the belief that hostile foreign governments and nongovernmental entities will endeavor to impair America's space capabilities or use satellites to their own advantage. How prepared is the country for this day? What in some respects may be called America's second Manifest Destiny, beginning in earnest some forty years ago, has sparked a great revolution in the international security environment. Man's activities in space have transformed the dark arena surrounding Earth into a traversable medium having increasing influence over strategic interests and defense planning. The universal application of space power and the speed and singular contributions of satellite operations help the country cope with many traditional security matters in ways that are unique to the space age, a development that has encouraged the evolution of new war-fighting concepts and doctrines.